Ileal gallstone obstruction: Single-balloon enteroscopic removal - Heinzow, Hauke Sebastian (Baishideng Publishing Group Co., Limited, 2010)
Gallstone-induced ileus is a rare complication of cholelithiasis. Since localization of gallstones impacted in the small bowel, especially in the ileum, prevents access by conventional endoscopy in most cases, the mainstay of treatment remains surgical. Recent invention of double- and single-balloon enteroscopy has added much to the ability of imaging the small bowel and enables endoscopically directed therapy. Herein, for the first time, we report a successful endoscopic calculus removal via peroral single-balloon enteroscopy in an 81-year-old woman suffering from gallstone ileus of the ileum.